INFLAMMATORY INDEX AND TREATMENT OF BRAIN ABSCESS - OYAMA, HIROFUMI (Nagoya J Med Sci, 2012)
This study retrospectively analyzed 12 patients with brain abscesses. Half of the patients were diagnosed inaccurately in the initial stage, and 7.2 days were required to achieve the final diagnosis of brain abscess. The patients presented only with a moderately elevated leukocyte count, serum CRP levels, or body temperatures during the initial stage. These markers changed, first with an increase in the leukocyte count, followed by the CRP and body temperature. The degree of elevation tended to be less prominent, and the time for each inflammatory index to reach its maximum value tended to be longer in the patients without ventriculitis than in those with it. The causative organisms of a brain abscess were detected in 10 cases. The primary causative organisms from dental caries were Streptococcus viridians or milleri, and Fusobacterium nucleatum. Nocardia sp. or farcinica were common when the abscess was found in other regions. The primary causative organisms of unrecognized sources of infection were Streptococcus milleri and Prolionibacterium sp. Nocardia is resistant to many antibiotics. However, carbapenem, tetracycline and quinolone were effective for Nocardia as well as many other kinds of bacteria. In summary, the brain abscesses presented with only mildly elevated inflammatory markers of body temperature, leukocyte and CRP. These inflammatory markers were less obvious in the patients without ventriculitis and/or meningitis. The source of infection tended to suggest some specific primary causative organism. It was reasonable to initiate therapy with carbapenem.